Molecular dynamics simulations and membrane protein structure quality. - Ivetac, A; Sansom, MS (2008)
Despite a growing repertoire of membrane protein structures (currently approximately 120 unique structures), considerations of low resolution and crystallization in the absence of a lipid bilayer require the development of techniques to assess the global quality of membrane protein folds. This is also the case for assessment of, e.g. homology models of human membrane proteins based on structures of (distant) bacterial homologues. Molecular dynamics (MD) simulations may be used to help evaluate the quality of a membrane protein structure or model. We have used a structure of the bacterial ABC transporter MsbA which has the correct transmembrane helices but an incorrect handedness and topology of their packing to test simulation methods of quality assessment. An MD simulation of the MsbA model in a lipid bilayer is compared to a simulation of another bacterial ABC transporter, BtuCD. The latter structure has demonstrated good conformational stability in the same bilayer environment and over the same timescale (20 ns) as for the MsbA model simulation. A number of comparative analyses of the two simulations were performed to assess changes in the structural integrity of each protein. The results show a significant difference between the two simulations, chiefly due to the dramatic structural deformations of MsbA. We therefore propose that MD could become a useful quality control tool for membrane protein structural biology. In particular, it provides a way in which to explore the global conformational stability of a model membrane protein fold.